2017
DOI: 10.18203/2394-6040.ijcmph20170758
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of under-five immunization coverage among the population of slum areas in Mangalore taluk, India

Abstract: Background: Immunization coverage is better in urban than rural areas. However, we anticipate and argue that within the urban areas disparities and inequities persist in immunization coverage and that the socioeconomically disadvantaged, particularly those who reside in slum areas are more vulnerable and may contribute to the lower uptake of immunization. The objectives of the study were to assess the under-five immunization coverage amongst the households in slums of Mangalore taluk and to identify determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
5
11
1
Order By: Relevance
“…11,12 Our study found slight male preponderance (56.3%) which was in congruence with studies by, Kumar et al, Srikanth et al, Awasthi et al and Prinja et al at 56.5%, 56.6%, 55.7%, and 55.8%. 9,[13][14][15] More than two-thirds of participants in the present study belonged to joint family structure which was in line with research by Goyal et al 16 60.7% of children in our study ere of first birth order which was also observed by Dutta et al at 63.6%. 17 Institutional deliveries accounted for 95.2% which follows the pattern indicated in researches by Gill et al, Srikanth et al and Singh et al at 97.1, 98.8 and 95.1 percentages respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…11,12 Our study found slight male preponderance (56.3%) which was in congruence with studies by, Kumar et al, Srikanth et al, Awasthi et al and Prinja et al at 56.5%, 56.6%, 55.7%, and 55.8%. 9,[13][14][15] More than two-thirds of participants in the present study belonged to joint family structure which was in line with research by Goyal et al 16 60.7% of children in our study ere of first birth order which was also observed by Dutta et al at 63.6%. 17 Institutional deliveries accounted for 95.2% which follows the pattern indicated in researches by Gill et al, Srikanth et al and Singh et al at 97.1, 98.8 and 95.1 percentages respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly higher odds of no immunization for females was observed in study by Patel et al, Francis et al, and Shrivastwa et al at 1.63, 1.16, and 1.2 respectively. 5,30,31 Similar to current study place of delivery was significant for researches by Devendra et al and Rajat et al 29,32 In congruence with the present study urban residence had higher odds (1.23) of partial immunization as observed by Prinja et al 15 For mother's education, trend similar to our study was observed by Gupta et al (OR-5.8 in favor of illiterate) and Francis et al 7,30 Similar to current study mothers' occupation was significant in studies by Kumar et al and Awasthi et al 9,14 In congruence with present study Nath et al observed no immunization associated with low socioeconomic status (OR-10.8). 33 Similar to our research joint families favored no immunization in study by Nath et al with OR at 2.1.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Among the individual vaccines, it was found that the immunization status for BCG & OPV-0 was highest, which was similar to the findings from most of the other studies. [17][18][19][20][21] These are the vaccines given at the time of birth, and the highest percentage of vaccination for these is justified as institutional delivery was reported by most, i.e., at Government and private hospitals. Immunization status for subsequent vaccines showed a downtrend.…”
Section: Discussionmentioning
confidence: 99%